2011
DOI: 10.1186/1297-9716-42-74
|View full text |Cite
|
Sign up to set email alerts
|

A single vaccination of commercial broilers does not reduce transmission of H5N1 highly pathogenic avian influenza

Abstract: Vaccination of chickens has become routine practice in Asian countries in which H5N1 highly pathogenic avian influenza (HPAI) is endemically present. This mainly applies to layer and breeder flocks, but broilers are usually left unvaccinated. Here we investigate whether vaccination is able to reduce HPAI H5N1 virus transmission among broiler chickens. Four sets of experiments were carried out, each consisting of 22 replicate trials containing a pair of birds. Experiments 1-3 were carried out with four-week-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Differences in MDA's half-life between the vaccinated and unvaccinated groups may suggest a possible interference of MDAs with the induction of the humoral response by AI vaccines. Indeed, MDA's such interference with the development of an immune response against various antigens has been recorded after the application of inactivated vaccines (Poetri et al, 2011). On the other hand, MDA against HVT is present in commercial DOCs.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in MDA's half-life between the vaccinated and unvaccinated groups may suggest a possible interference of MDAs with the induction of the humoral response by AI vaccines. Indeed, MDA's such interference with the development of an immune response against various antigens has been recorded after the application of inactivated vaccines (Poetri et al, 2011). On the other hand, MDA against HVT is present in commercial DOCs.…”
Section: Discussionmentioning
confidence: 99%
“…This goal may be achieved using inactivated influenza virus vaccines [16], [17], [50]. However, there are also examples showing that inactivated vaccines sometimes fail to prevent virus shedding, especially if birds were immunized only once, or if the vaccine strain did not adequately match the HA antigen of the challenge virus [14], [51]. Interestingly, vaccination of chickens with recombinant VRPs expressing HA H5-HP (clade 2.5) abolished cloacal and oropharyngeal shedding of A/whooper swan/Mongolia/3/2005 (clade 2.2).…”
Section: Discussionmentioning
confidence: 99%
“…These vaccines have the advantage of being safe, but they also come with a number of shortcomings. For example, inactivated vaccines have to be repeatedly applied to induce full-protective and long-lasting immune responses in poultry [14]. Because inactivated influenza virus vaccines do not provide danger signals that would sufficiently trigger innate immunity, they are often formulated and applied with adjuvants [15][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, H5N1 virus can replicate in clinically healthy vaccinated birds, while vaccine pressure can give rise to antigenic drift (Lee, Senne, and Suarez 2004;Peyre et al 2009). Vaccination of broiler chickens did not reduce HPAI H5N1transmission, and the authors pointed out that this was most likely due to interference of maternal immunity (Poetri et al 2011). A case-control study in the Red River Delta Region in Vietnam found that higher numbers of broiler flocks in the village increased the HPAI risk (Desvaux et al 2011).…”
Section: Future Pandemic Potentialmentioning
confidence: 98%